Changes of soil organic carbon and aggregate stability along elevation gradient in Cunninghamia lanceolata plantations - Xiaoqing Cao; Yuting Xu; Fei Wang; Zhili Zhang; Xiaoniu Xu (Scientific Reports)
Abstract Exploring the components of soil organic carbon (SOC) and aggregate stability across different elevations is crucial to assessing the stability of SOC in subtropical forest ecosystems under climate change. In this study, we investigated the spatial variation of active carbon (C) compositions, aggregate distribution, and stability in Chinese fir (Cunninghamia lanceolata) plantations across an elevation gradient from 750 to 1150 m a.s.l. on the northern foothills of the Dabie Mountains, China. The results showed that macroaggregates accounted for more than 80% of all fractions at different elevations. In the 0–10 cm soil layer, the macroaggregates, mean weight diameter (MWD), geometric mean diameter (GMD), and SOC exhibited a U-shaped distribution trend with increasing elevation. Conversely, in the 10–50 cm soil layer, these indicators showed a consistent increasing trend. Similarly, the contents of easily oxidizable carbon (EOC) and particulate organic carbon (POC) gradually increased with increasing elevation. Microbial biomass carbon (MBC) and silt + clay C exhibited a unimodal distribution pattern along the elevational gradient, peaking at 850 m a.s.l., which is mainly related to soil pH and C/N ratio. Across all elevations, The silt + clay C was significantly higher than that of macro- and micro-aggregate C. Macro- and micro-aggregate C, and dissolved organic carbon (DOC) were significantly positively correlated with MWD. The results demonstrated that elevation and soil layer have significant effects on SOC and aggregate stability. The physical protection of silt + clay fractions and the active carbon pools may be the main mechanisms for organic carbon preservation in the Dabie Mountains. These results contribute to further deepening the impact of elevation on climate change and the C cycling of forest ecosystems.